RELEVANSI TEORI BELAJAR BEHAVIORISTIK TERHADAP NILAI-NILAI DALAM AJARAN YOGA - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Learning theory is a theory in which there is an application of teaching and learning activities between teachers and students, the design of learning methods that will be implemented in class and outside the classroom. The theories of learning explain what learning and how to learn it happens. In this case behavioristic learning theory is a theory that learning is a change in behavior as a result of interaction between stimulus and response. This theory of learning is precisely used today considering the still relevance of the behavioristic learning theory with the innovative things though it is with spiritual related things as an example of Yoga. Behavioristic learning theory is in line with the values in the Yoga teaching of Karma Yoga, Bakti Yoga, Jnana Yoga, and the king of Yoga. The teaching of Yoga teaches people to always reach their divisions through various ways such as addressing the problem well as the teachings of Karma Yoga, through respecting God's creations such as the teaching of Bakti Yoga, through learning as a medium A change of attitude from those who do not know to know like Jnana Yoga teaching, as well as the discipline of the teachings of the king of Yoga. All these things are reflected in the understanding of the Behavioristic learning theory that is a better process or behavior change in direction.